Influence of xenobiotics on the luminescence of Vibrio harveyi strains isolated from Cuban marine waters - Lugioyo Gallardo, Gladys Margarita (2024)
Toxicity tests using luminescent bacteria are promising tools to assess the quality of aquatic environments given the high sensitivity of these bacteria to pollutants. The research evaluated the effect of different types of xenobiotics—salts of mercury, copper, chromium, silver, iron, and four pesticides—on the luminescence of Vibrio harveyi strains CBM-784, CBM-976, and CBM-992, isolated from waters of the Cuban platform. The selected strains showed a reduction in luminescent emission at 15 min of exposure to the tested compounds, with a consistent, decreasing sequence of toxicity for all three strains as follows: HgCl2 > CuSO4 ≈ Cuproflow > K2Cr2O7 > Sphere Max ≈ Kospi-sc 130 > AgNO3 > Fe2(SO4)3 > Envidor. Results suggest that these cultures could be used to design a contamination biosensor since luminescence responds to nanomolar concentrations of the tested toxicants.